2021
DOI: 10.1007/s12975-021-00957-7
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Endovascular Treatments for Intracranial Atherosclerotic Stenosis: A Network Meta-Analysis

Abstract: Medical treatment and endovascular therapy are widely used for intracranial atherosclerotic stenosis, but the best treatment strategy remains uncertain. The goal of this study was to compare the safety and effectiveness of medical treatment, stenting, and primary balloon angioplasty (PBA). We searched PubMed, MEDLINE, and EMBASE for trials comparing these three treatments for intracranial stenosis up to December 24, 2020. We performed a network meta-analysis with randomeffects models. The primary outcome was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The incidence rate was lower than that reported in previous studies (SAMMPRIS, 14.7% within 30 days and 19.7% within 1 year; VISSIT, 24.1% within 30 days and 36.2% within 1 year; and CASSIS, 5.1% within 30 days and 8% within 1 year). Previous meta-analyses have also suggested that SBA and medical therapy have similar short-term outcomes; however, SBA may better prevent long-term stroke recurrence (12). Thus, we hypothesized that SBA plus medical therapy may outperform medical therapy alone in patients with minor stroke/ TIA with ICAS within 1 week of onset who are at a high risk of recurrence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The incidence rate was lower than that reported in previous studies (SAMMPRIS, 14.7% within 30 days and 19.7% within 1 year; VISSIT, 24.1% within 30 days and 36.2% within 1 year; and CASSIS, 5.1% within 30 days and 8% within 1 year). Previous meta-analyses have also suggested that SBA and medical therapy have similar short-term outcomes; however, SBA may better prevent long-term stroke recurrence (12). Thus, we hypothesized that SBA plus medical therapy may outperform medical therapy alone in patients with minor stroke/ TIA with ICAS within 1 week of onset who are at a high risk of recurrence.…”
Section: Discussionmentioning
confidence: 95%
“…Over the past 20 years, several trials have investigated stent placement combined with medical therapy in this population; however, the results have been neutral, and the risk of recurrent stroke remains high (9)(10)(11). Compared with stenting, submaximal balloon angioplasty (SBA) could be a safer and simpler intervention that may be an effective strategy for preventing recurrent stroke (12,13). For example, prior meta-analysis found that the incidence of stroke or death within 30 days after SBA was 3-4.9% (14,15), and the one-year stroke occurrence rate was 5% (15), which was lower than that of stent placement (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The ndings revealed that balloon angioplasty signi cantly reduced short-term risks of stroke and death compared to the latter two methods (perioperative or ≤ 3 months postoperative) 23 . A meta-analysis comparing medical treatment, stent placement, and balloon angioplasty for sICAS indicated that, during long-term follow-ups, balloon angioplasty might be the most effective method for preventing strokes and reducing mortality 24 . These results suggest that in the current clinical context, balloon angioplasty may be considered the optimal method for managing sICAS.…”
Section: Discussionmentioning
confidence: 99%
“…7 Three recent meta-analyses all suggested that submaximal balloon angioplasty may be a potentially promising intervention for sICAS. [8][9][10] However, compared with medical therapy, the long-term effectiveness of balloon angioplasty, including recurrent stroke and restenosis of target vessels, is still unknown. Therefore, we designed the BASIS trial to investigate a new perspective on endovascular treatment for sICAS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several previous meta-analyses also proved the safety and efficacy of balloon angioplasty for sICAS, which suggested that balloon angioplasty alone may be potentially promising for sICAS. [8][9][10] To date, limited evidence is available from randomised controlled trials (RCTs) to determine the safety and efficacy of balloon angioplasty for patients with sICAS. Hence, we designed the Balloon Angioplasty for Symptomatic Intracranial Artery Stenosis (BASIS) RCT to explore whether balloon angioplasty plus AMM is superior to AMM alone in patients with sICAS.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%